let X be set ; :: thesis: for S being SigmaField of X

for M being sigma_Measure of S

for G, F being sequence of S st M . (F . 0) < +infty & G . 0 = {} & ( for n being Nat holds

( G . (n + 1) = (F . 0) \ (F . n) & F . (n + 1) c= F . n ) ) holds

M . (meet (rng F)) = (M . (F . 0)) - (sup (rng (M * G)))

let S be SigmaField of X; :: thesis: for M being sigma_Measure of S

for G, F being sequence of S st M . (F . 0) < +infty & G . 0 = {} & ( for n being Nat holds

( G . (n + 1) = (F . 0) \ (F . n) & F . (n + 1) c= F . n ) ) holds

M . (meet (rng F)) = (M . (F . 0)) - (sup (rng (M * G)))

let M be sigma_Measure of S; :: thesis: for G, F being sequence of S st M . (F . 0) < +infty & G . 0 = {} & ( for n being Nat holds

( G . (n + 1) = (F . 0) \ (F . n) & F . (n + 1) c= F . n ) ) holds

M . (meet (rng F)) = (M . (F . 0)) - (sup (rng (M * G)))

let G, F be sequence of S; :: thesis: ( M . (F . 0) < +infty & G . 0 = {} & ( for n being Nat holds

( G . (n + 1) = (F . 0) \ (F . n) & F . (n + 1) c= F . n ) ) implies M . (meet (rng F)) = (M . (F . 0)) - (sup (rng (M * G))) )

assume that

A1: M . (F . 0) < +infty and

A2: ( G . 0 = {} & ( for n being Nat holds

( G . (n + 1) = (F . 0) \ (F . n) & F . (n + 1) c= F . n ) ) ) ; :: thesis: M . (meet (rng F)) = (M . (F . 0)) - (sup (rng (M * G)))

for n being Nat holds G . n c= G . (n + 1) by A2, MEASURE2:13;

then M . (union (rng G)) = sup (rng (M * G)) by MEASURE2:23;

hence M . (meet (rng F)) = (M . (F . 0)) - (sup (rng (M * G))) by A1, A2, Th6; :: thesis: verum

for M being sigma_Measure of S

for G, F being sequence of S st M . (F . 0) < +infty & G . 0 = {} & ( for n being Nat holds

( G . (n + 1) = (F . 0) \ (F . n) & F . (n + 1) c= F . n ) ) holds

M . (meet (rng F)) = (M . (F . 0)) - (sup (rng (M * G)))

let S be SigmaField of X; :: thesis: for M being sigma_Measure of S

for G, F being sequence of S st M . (F . 0) < +infty & G . 0 = {} & ( for n being Nat holds

( G . (n + 1) = (F . 0) \ (F . n) & F . (n + 1) c= F . n ) ) holds

M . (meet (rng F)) = (M . (F . 0)) - (sup (rng (M * G)))

let M be sigma_Measure of S; :: thesis: for G, F being sequence of S st M . (F . 0) < +infty & G . 0 = {} & ( for n being Nat holds

( G . (n + 1) = (F . 0) \ (F . n) & F . (n + 1) c= F . n ) ) holds

M . (meet (rng F)) = (M . (F . 0)) - (sup (rng (M * G)))

let G, F be sequence of S; :: thesis: ( M . (F . 0) < +infty & G . 0 = {} & ( for n being Nat holds

( G . (n + 1) = (F . 0) \ (F . n) & F . (n + 1) c= F . n ) ) implies M . (meet (rng F)) = (M . (F . 0)) - (sup (rng (M * G))) )

assume that

A1: M . (F . 0) < +infty and

A2: ( G . 0 = {} & ( for n being Nat holds

( G . (n + 1) = (F . 0) \ (F . n) & F . (n + 1) c= F . n ) ) ) ; :: thesis: M . (meet (rng F)) = (M . (F . 0)) - (sup (rng (M * G)))

for n being Nat holds G . n c= G . (n + 1) by A2, MEASURE2:13;

then M . (union (rng G)) = sup (rng (M * G)) by MEASURE2:23;

hence M . (meet (rng F)) = (M . (F . 0)) - (sup (rng (M * G))) by A1, A2, Th6; :: thesis: verum